2018
DOI: 10.1016/j.jcmgh.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Adipose-derived Stromal Cells From Crohn’s Disease Patients Induce Protective Effects in Colonic Epithelial Cells and Mice With Colitis

Abstract: Mesenteric adipose tissue hyperplasia is a hallmark of Crohn’s disease (CD). Recently, we showed that mesenteric adipose-derived stromal cells (ADSCs) from CD, ulcerative colitis, and control patients synthesize and release adipokines in a disease-dependent manner. Here we examined the expression profiles of CD and control patient-derived mesenteric ADSCs and studied the effects of their extracellular mediators on colonocyte signaling in vitro and experimental colitis in vivo. ADSCs were isolated from mesenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Recently, in an interesting study, Hoffman et al [214] demonstrated that mesenteric adipose-derived stromal cells from CD patients could exert beneficial protective effects on the disease activity and severity of mice with experimental colitis. Because of the potential pathogenic role of adipose tissue and adipokines in development of IBD, some experimental studies attempt to reduce colitis severity by reducing the total or particular organ obesity.…”
Section: Year Study Type Conclusionmentioning
confidence: 99%
“…Recently, in an interesting study, Hoffman et al [214] demonstrated that mesenteric adipose-derived stromal cells from CD patients could exert beneficial protective effects on the disease activity and severity of mice with experimental colitis. Because of the potential pathogenic role of adipose tissue and adipokines in development of IBD, some experimental studies attempt to reduce colitis severity by reducing the total or particular organ obesity.…”
Section: Year Study Type Conclusionmentioning
confidence: 99%
“…Despite different sources, MSCs have common features and behavioral traits, which not only provide cells for tissue reconstitution but also regulate inflammation and “educate” other cells to facilitate tissue repair[ 22 ]. Accumulating evidence suggests a therapeutic effect of MSCs in IBD[ 23 , 24 ] and ADSCs have been widely used because of their easy acquisition. In 2005, the first phase I clinical trial showed that 75% of fistulas were healed by ADSC therapy without any side effects[ 25 ], which opened the window to ADSC therapy for CD.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric adipose tissue (MAT) hyperplasia is a hallmark of CD. Mesenteric adipose-derived stromal cells (ADSCs) synthesize and release adipokines in a disease-dependent manner and alter colonic epithelial cell signaling [201].Transmural inflammation facilitates bacterial translocation into the creeping fat, which exerts a protective effect via a localized anti-inflammatory effect, thus preventing a systemic inflammatory response in CD [202].…”
Section: Colitismentioning
confidence: 99%